ICELANDITIC JURASSIC VOLCANITE COMPLEX OF MALYY CAUCASUS - Ostroumova A.S.; Tsenter I.Y.; Avdeev A.G. (My University, 1991)
A Bathonian volcanogenic unit in northern Karabakh was examined. It was established that it belongs to a tholeiitic series of the ferruginous moderately highly titaniferous type. Two complexes were identified: an early complex of tholeiitic basalts - andesibasalts - andesites, and a late complex of icelandites - ferrodacites - ferrorhyolites. The average chemical compositions of the rocks in both complexes and the amounts of rare and dispersed elements in them were described. The icelandite complex was interpreted as the manifestation of volcanism in the frontal part of an ensimatic island arc.
Keywords: Jurassic; Mesozoic::Jurassic; Мезозой::Юрская